Dioxygen and reactive oxygen species' paramagnetic properties are important factors in dermatology - BF Minaev (International Journal of Dermatology and Clinical Research - Peertechz Publications, 2022)
Dioxygen (the O2 molecule) is an important component of all tissues including skin. Even small fluctuations of O2 amount (dioxygen concentration changes in the tissue microenvironment) can strongly affect the signaling functions of cells through the reactive oxygen species (ROSs) activity and hence - the whole cellular metabolism, the cell proliferation, and differentiation, etc [1,2].